DINAMIKA TRADISIONALISASI DALAM PENDIDIKAN PESANTREN DI ERA GLOBALISASI - Kurniasih, Nia; Basri, Hasan; Suhartini, Andewi (Sindoro: Cendikia Pendidikan, 2024)
This article analyzes the efforts of Islamic boarding schools in maintaining their traditional values ​​amidst the flow of modernization. This descriptive qualitative research uses a literature review method to examine various strategies implemented by Islamic boarding schools. The results of the study indicate that traditionalization is a strategic effort to maintain the relevance of Islamic educational institutions in the modern era. Integration of tradition-based curriculum, wise use of technology, and strengthening of Islamic boarding school culture are the keys to success in balancing between maintaining identity and responding to the challenges of the times. This study highlights the importance for Islamic boarding schools to remain rooted in tradition but still be able to adapt to changing times. Keyword: pesantren, traditionalization, modernization, traditional values, identity, balance, strategy, impact